Analysing the efficiency of health systems: a systematic review of the literature - Mbau, R; Musiega, A; Nyawira, L; Tsofa, B; Mulwa, A; Molyneux, S; Maina, I; Jemutai, J; Normand, C; Hanson, K; Barasa, E (Springer, 2022)
Background Efficiency refers the use of resources in ways that optimise desired outcomes. Health system efficiency is a priority concern for policy makers globally as countries aim to achieve universal health coverage, and face the additional challenge of an aging population. Efficiency analysis in the health sector has typically focused on the efficiency of healthcare facilities (hospitals, primary healthcare facilities), with few studies focusing on system level (national or sub-national) efficiency. We carried out a thematic review of literature that assessed the efficiency of health systems at the national and sub-national level.